1997
DOI: 10.1073/pnas.94.12.6512
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic stimulation alters performance and task-specific regional cerebral blood flow during working memory

Abstract: Modulation of the cholinergic neurotransmitter system results in changes in memory performance, including working memory (WM), in animals and in patients with Alzheimer disease. To identify associated changes in the functional brain response, we studied performance measures and regional cerebral blood f low (rCBF) using positron emission tomography (PET) in healthy subjects during performance of a WM task. Eight control subjects received an infusion of saline throughout the study and 13 experimental subjects r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
81
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(91 citation statements)
references
References 38 publications
9
81
0
1
Order By: Relevance
“…These results indicate a role for PRh ACh in the acquisition, but not retrieval, of object information. Accordingly, evidence from human studies suggests that increased cortical ACh can enhance the selectivity of perceptual processing in the extrastriate cortex during encoding in a visual working memory task (Furey et al, 1997(Furey et al, , 2000, and scopolamine has been shown to reduce encodingrelated activity in the temporal lobes (including PRh) during visual delayed matching to sample (Schon et al, 2005). Moreover, reports indicate that direct application of cholinergic agents can fine-tune the receptive fields of cortical pyramidal cells (Krnjevic and Phillis, 1963;Sillito and Kemp, 1983;Murphy and Sillito, 1991;Rasmusson, 2000), and such findings have long been suggested as evidence for a role of cortical ACh in facilitating information acquisition, perhaps by amplifying the cortical processing of sensory stimuli (Hasselmo and Bower, 1993;Everitt and Robbins, 1997;Sarter and Bruno, 1997;Weinberger, 2003;Hasselmo and McGaughy, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate a role for PRh ACh in the acquisition, but not retrieval, of object information. Accordingly, evidence from human studies suggests that increased cortical ACh can enhance the selectivity of perceptual processing in the extrastriate cortex during encoding in a visual working memory task (Furey et al, 1997(Furey et al, , 2000, and scopolamine has been shown to reduce encodingrelated activity in the temporal lobes (including PRh) during visual delayed matching to sample (Schon et al, 2005). Moreover, reports indicate that direct application of cholinergic agents can fine-tune the receptive fields of cortical pyramidal cells (Krnjevic and Phillis, 1963;Sillito and Kemp, 1983;Murphy and Sillito, 1991;Rasmusson, 2000), and such findings have long been suggested as evidence for a role of cortical ACh in facilitating information acquisition, perhaps by amplifying the cortical processing of sensory stimuli (Hasselmo and Bower, 1993;Everitt and Robbins, 1997;Sarter and Bruno, 1997;Weinberger, 2003;Hasselmo and McGaughy, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, physostigmine administration has changed the level of arousal and selective attention to visual tasks in pattern-flash stimulus tests in human PET studies of elderly subjects (Mentis et al, 2001). In a cerebral blood flow study, with healthy human volunteers (age range 22-68 years), physostigmine was associated with improved WM efficiency as indicated by faster reaction times in a WM task for faces, and by reduced activation of cortical regions associated with WM (Furey et al, 1997). Another recent study of the cholinesterase inhibitor tetrahydroaminoacridine (THA) in young and aged healthy monkeys showed enhanced visual divided attention performance, measured via a computer task requiring simultaneous tracking of two visual targets (O'Neill et al, 1999).…”
Section: Acetylcholinesterase Inhibitorsmentioning
confidence: 99%
“…mine was associated with increased extrastriate activation but decreased prefrontal activation (Furey et al, 1997(Furey et al, , 2000a.…”
Section: Neuroimaging Findingsmentioning
confidence: 99%